Montelukast Ameliorates Antimony-Induced Neurotoxicity Accompanied by Alterations in Oxidative Stress, Neuroinflammation, and Mitochondrial Function - Atul; Surbhi Gupta; Sachin Tyagi; Chhavi Panwar; Vishal Panwar; Prabhat Singh (Biological Trace Element Research, 2026)

In silico retrieval of sulfiredoxin from Setaria italica, Panicum miliaceum, and Eleusine coracana: Sequence characterization, structural modeling, and protein–protein interaction analysis - Rahul Thakur; Arvind Gupta; Kanchan Rauthan; Deepti Dixit; Arzoo Choudhary; Ashutosh Kumar Pandey; Atul Krishna Dev; Saurabh Yadav (Plant Gene, 2026)

Long-Term Assessment of Near-Surface Air Pollutants at Jaipur: Source Identifications and Their Association with Surface Meteorology - Akanksha Gupta; Atul Kumar Srivastava; Deewan Singh Bisht; Charu Jhamaria (Pure and Applied Geophysics, 2026)

Landslide susceptibility assessment using AHP and RF techniques: Special reference to Kumaun lesser Himalaya, Uttarakhand, India - Achla Joshi; Girish Ch Kothyari; Atul Kumar Patidar; Khyati Gupta (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Ligilactobacillus salivarius and Limosilactobacillus reuteri improve growth and intestinal health in broilers via modulating gut microbiota and immune response - Neha Chavan; Mahesh Gupta; Krushna Bibichand Bahiram; Jayant Pandurang Korde; Mukund Kadam; Atul Dhok; Sachin Kumar (Research in Veterinary Science, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

Improved performance of Andrographis paniculata in litchi-based agroforestry systems - Aseem Khan; Yamini Sharma; Prem Prakash Sharma; Aman Deep Ranga; Ankita Bhatia; Devansh Dogra; Atul Gupta (Agroforestry Systems, 2025)

Advancing sustainable food Packaging: Integrating machine learning, deep learning, and artificial intelligence - Jyoti; Atul K. Gupta; Ashok Kumar; Bhuvnesh Kumar (Trends in Food Science & Technology, 2025)

An environmentally benign process to synthesize vanillin and other substituted phenyl aldehydes using natural phenylpropenes - Sarita Singh; Swati Singh; Asha Budakoti; Neha Kumari; Ram Swaroop Verma; Arvind Singh Negi; Karuna Shanker; Sudeep Tandon; Alok Kalra; Atul Gupta (Food Chemistry, 2025)

Intensification mechanisms and moisture dynamics of super cyclonic storm ‘Amphan’ over the Bay of Bengal: Implications for aerosol re-distribution - Vivek Singh; Atul Kumar Srivastava; Anu Gupta; Rakesh Teja Konduru; Amarendra Singh; Sumit Singh; Arun Kumar; Deewan Singh Bisht; Abhay Kumar Singh (Science of The Total Environment, 2024)

Neoproterozoic crustal evolution of Indo-Australo-Antarctic Suture domain and Gamburtsev Subglacial Mountains, East Antarctica: Insights from offshore sediments - Rashmi Gupta; Mayuri Pandey; Devsamridhi Arora; Akash K. Pandey; Naresh C. Pant; K. Batuk Joshi; Pankaj Kumar; M. Satyanarayanan; Atul Singh (Gondwana Research, 2024)

Assessment of higher demand of household energy consumption in different households in India: an inter-comparative study and solar savings valuation - Abhishek Saxena; Atul A. Sagade; Erdem Cuce; Desh Bandhu Singh; Avnish Kumar; Parul Gupta (Environmental Science and Pollution Research, 2024)

Assessment of Trachyspermum ammi essential oil against Aspergillus flavus, aflatoxin B1 contamination, and post-harvest quality of Sorghum bicolor - Prem Pratap Singh; Atul Kumar Jaiswal; Ritu Singh; Akshay Kumar; Vishal Gupta; Tanya Singh Raghuvanshi; Angad Sharma; Bhanu Prakash (Food Chemistry, 2024)

Co-movement between carbon emissions and forex market: A tale of COVID-19 outbreak and Russia-Ukraine invasion - Rabindra Nepal; Miklesh Prasad Yadav; Rupinder Katoch; Himani Gupta; Atul Kumar (Resources Policy, 2024)

Selective aerobic coupling of amines to imines using solar spectrum-responsive flower-like Nen-graphene quantum dots (GQDs) decorated with 2, 4-dinitrophenylhydrazine (PH) as a photocatalyst - Neetesh Kumar; Rajesh K. Yadav; Ahmad Umar; Ahmed A. Ibrahim; Satyam Singh; Rehana Shahin; Atul P. Singh; Abhishek K. Gupta; Navneet K. Gupta; Jin Ook Baeg; Dilip K. Dwivedi; Sotirios Baskoutas (Chemosphere, 2023)

Role of Shape and Kinematics in the Hydrodynamics of a Fish-like Oscillating Hydrofoil - Siddharth Gupta; Atul Sharma; Amit Agrawal; Mark C. Thompson; Kerry Hourigan (Journal of Marine Science and Engineering, 2023)
In the present two-dimensional numerical study, we investigate the roles of geometrical parameters of a hydrofoil (shape/curvature of the leading and trailing edges and thickness) and kinematic parameters (phase difference between heave and pitch (ϕ)) on the propulsive performance of different-shaped hydrofoils oscillating at maximum angles of attack up to αmax=30∘. The study was carried out at a fixed non-dimensional maximum heave to chord ratio h∘/C=0.75, Strouhal number St=0.25, and Reynolds number Re=5000. Our findings reveal that hydrofoil performance and stability improve with leading and trailing edge curvatures but decline as thickness increases. By analyzing the near-wake structure, we establish that even minimal flow separation increases power consumption while moderate flow separation enhances thrust. Over the range of different-shaped hydrofoils at different αmax and ϕ, maximum propulsion efficiency occurs for those parameters for which there is a small degree of flow separation but with no roll-up of a separating vortex. In comparison, maximum thrust generation occurs when there is a moderately strong flow separation but without induction of a significant amount of fluid around the trailing edge. These insights offer valuable knowledge for understanding fish propulsion efficiency and have applications in designing autonomous underwater vehicles (AUVs) and micro-air vehicles (MAVs).

Characterization of piggery farm waste-borne bacterial transposable elements associated with antimicrobial resistance phenotypes - Priyanka Kumari Thakur; Rajib Deb; Seema Rani Pegu; Ranjeet Parihar; Jagana Niharika; Pranab Jyoti Das; Gyanendra Singh Sengar; Joyshikh Sonowal; Parul Chaudhary; Arutkumaran Selvaradjou; Atul Raj; Vivek Kumar Gupta (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Assessing the role of ACC deaminase-producing bacteria in alleviating salinity stress and enhancing zinc uptake in plants by altering the root architecture of French bean (Phaseolus vulgaris) plants - Shikha Gupta; Sangeeta Pandey; Vashista Kotra; Atul Kumar (Planta, 2023)

Antioxidant additive melatonin in tris-based egg yolk extender improves post-thaw sperm attributes in Hariana bull - Dileep Kumar Yadav; Anuj Kumar; Shashikant Gupta; Pratishtha Sharma; Gyanesh Kumar; Vikas Sachan; Brijesh Yadav; Sarvajeet Yadav; Atul Saxena; Dilip Kumar Swain (Animal Reproduction Science, 2023)

Withania somnifera phytochemicals possess SARS-CoV-2 RdRp and human TMPRSS2 protein binding potential - Kumari Sunita Prajapati; Atul Kumar Singh; Prem Prakash Kushwaha; Mohd Shuaib; Santosh Kumar Maurya; Sanjay Gupta; Sabyasachi Senapati; Surya Pratap Singh; Mohammad Waseem; Shashank Kumar (Vegetos, 2022)

Genomic characterization of ZIP genes in pigeonpea (CcZIP) and their expression analysis among the genotypes with contrasting host response to pod borer - Atul Nag; Kapil Gupta; Neeraj Dubey; Sujit K. Mishra; Jogeswar Panigrahi (Physiology and Molecular Biology of Plants, 2021)

Micro-array Analysis of Cold Tolerant Tomato Expressing Nicotiana tabacum Osmotin - Vikas Yadav Patade; Atul Grover; Anukriti; Sanjay Mohan Gupta; M. Nasim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Role of ZBTB7A zinc finger in tumorigenesis and metastasis - Atul Kumar Singh; Shiv Verma; Prem Prakash Kushwaha; Kumari Sunita Prajapati; Mohd Shuaib; Shashank Kumar; Sanjay Gupta (Molecular Biology Reports, 2021)

Unfolding antifungals: as a new foe to pancreatic ductal adenocarcinoma—a mini-review - Shruti Gupta; Atul Kumar; Kiran Kumar Tejavath (Molecular Biology Reports, 2021)

Retraction Note: Engineered Polyallylamine Nanoparticles for Efficient In Vitro Transfection - Atul Pathak; Anita Aggarwal; Raj K. Kurupati; Soma Patnaik; Archana Swami; Yogendra Singh; Pradeep Kumar; Suresh P. Vyas; Kailash C. Gupta (Pharmaceutical Research, 2020)

The impact of northern Indian Ocean rivers on the Bay of Bengal using NEMO global ocean model - Atul Srivastava; Anitha Gera; Imran M. Momin; Ashis Kumar Mitra; Ankur Gupta (Acta Oceanologica Sinica, 2020)

Combined Hepatoprotective Activity of Murraya koenigii and Phyllanthus niruri Extracts Against Paracetamol Induced Hepatotoxicity in Alcoholic Rats - Pallavi Shah; S. P. Singh; Atul Kumar Gupta; Anil Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Silkworm disease incidence trends during the years 1992–2011 in the Murshidabad district of West Bengal, India - Zakir Hossain; Satadal Chakraborty; Sunil Kumar Gupta; Atul Kumar Saha; Bharat Bhushan Bindroo (International Journal of Tropical Insect Science, 2017)

De Novo Assembly and Characterization of Developing Spikes Transcriptome of Finger Millet (Eleusine coracana): a Minor Crop Having Nutraceutical Properties - Anil Kumar; Vikram Singh Gaur; Anshita Goel; Atul Kumar Gupta (Plant Molecular Biology Reporter, 2015)

Overexpression of NAC gene from Lepidium latifolium L. enhances biomass, shortens life cycle and induces cold stress tolerance in tobacco: potential for engineering fourth generation biofuel crops - Atul Grover; Sadhana Singh; Pankaj Pandey; Vikas Yadav Patade; Sanjay Mohan Gupta; M. Nasim (Molecular Biology Reports, 2014)

RNAi Mediated curcin precursor gene silencing in Jatropha (Jatropha curcas L.) - Vikas Yadav Patade; Deepti Khatri; Kamal Kumar; Atul Grover; Maya Kumari; Sanjay Mohan Gupta; Devender Kumar; Mohammed Nasim (Molecular Biology Reports, 2014)

Analysis of Jatropha curcas transcriptome for oil enhancement and genic markers - Atul Grover; Maya Kumari; Sadhana Singh; Shivender Singh Rathode; Sanjay Mohan Gupta; Pankaj Pandey; Sween Gilotra; Devender Kumar; Mohommad Arif; Zakwan Ahmed (Physiology and Molecular Biology of Plants, 2014)

Surface Plasmon Resonance Sensogram Based Characterization of Antibodies Raised Against Intact Teliospores and Purified Diagnostic Antigen for Development of Nano-Immunosensor for Fungal Spore Antigen of Karnal Bunt (Tilletia indica) of Wheat - Sadhna Singh; Sanjay Gupta; Atul Kumar Gupta; Manoj Singh; Anil Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Cloning, in silico characterization and induction of TiKpp2 MAP kinase in Tilletia indica under the influence of host factor(s) from wheat spikes - Atul K. Gupta; G. K. Joshi; J. M. Seneviratne; Dinesh Pandey; Anil Kumar (Molecular Biology Reports, 2013)

Cloning and characterization of GPAT gene from Lepidium latifolium L.: a step towards translational research in agri-genomics for food and fuel - Sanjay Mohan Gupta; Pankaj Pandey; Atul Grover; Vikas Yadav Patade; Sadhana Singh; Zakwan Ahmed (Molecular Biology Reports, 2013)

DRE-binding transcription factor gene (LlaDREB1b) is regulated by various abiotic stresses in Lepidium latifolium L. - Sanjay Mohan Gupta; Pankaj Pandey; P. S. Negi; V. Pande; Atul Grover; Vikas Y. Patade; Zakwan Ahmed (Molecular Biology Reports, 2013)

Studies on the life cycle of five microsporidian isolates and histopathology of the mid-gut of the silkworm Bombyx mori (Lepidoptera: Bombycidae) - Zakir Hossain; Sunil Kumar Gupta; Satadal Chakrabarty; Atul Kumar Saha; Bharat Bhushan Bindroo (International Journal of Tropical Insect Science, 2012)

Female plants of Hippophae salicifolia D. Don are more responsive to cold stress than male plants - Sanjay Mohan Gupta; Atul Grover; Pankaj Pandey; Zakwan Ahmed (Physiology and Molecular Biology of Plants, 2012)

Isolation and characterization of cold responsive NAC gene from Lepidium latifolium - Mohammad Aslam; Atul Grover; Vimlendu Bhushan Sinha; Beenish Fakher; Veena Pande; Patade Vikas Yadav; Sanjay Mohan Gupta; Sivalingam Anandhan; Zakwan Ahmed (Molecular Biology Reports, 2012)

Expression analysis of MAP2K9 and MAPK6 during pathogenesis of Alternaria blight in Arabidopsis thaliana ecotype Columbia - P. Kannan; Dinesh Pandey; Atul K. Gupta; H. Punetha; Gohar Taj; Anil Kumar (Molecular Biology Reports, 2012)

Understanding the differential nitrogen sensing mechanism in rice genotypes through expression analysis of high and low affinity ammonium transporter genes - Vikram Singh Gaur; U. S. Singh; Atul K. Gupta; Anil Kumar (Molecular Biology Reports, 2012)

Spatial distribution pattern analysis of Dof1 transcription factor in different tissues of three Eleusine coracana genotypes differing in their grain colour, yield and photosynthetic efficiency - Nidhi Gupta; Atul Kumar Gupta; Anil Kumar (Molecular Biology Reports, 2012)

Breaking seed dormancy in Hippophae salicifolia, a high value medicinal plant - Sanjay Mohan Gupta; Pankaj Pandey; Atul Grover; Zakwan Ahmed (Physiology and Molecular Biology of Plants, 2011)

Differential Expression of PBF Dof Transcription Factor in Different Tissues of Three Finger Millet Genotypes Differing in Seed Protein Content and Color - Nidhi Gupta; Atul Kumar Gupta; N. K. Singh; Anil Kumar (Plant Molecular Biology Reporter, 2011)

Coal fly ash utilization in agriculture: its potential benefits and risks - Rajeev Pratap Singh; Amit K. Gupta; M. Hakimi Ibrahim; Atul Kumar Mittal (Reviews in Environmental Science and Bio/Technology, 2010)

In vivo evaluation of substituted 3-phenyl,7-methoxy-benzopyrans as modified estrogens - Atul Gupta; Govind Keshri; M. M. Singh; Suprabhat Ray (Medicinal Chemistry Research, 2010)

Identification of biomarker for determining genotypic potential of nitrogen-use-efficiency and optimization of the nitrogen inputs in crop plants - Anil Kumar; Nidhi Gupta; Atul Kumar Gupta; Vikram Singh Gaur (Journal of Crop Science and Biotechnology, 2009)

In vivo evaluation of substituted 2,3-diaryl acrylophenone amide derivatives as anti-implantation agents - Atul Gupta; Govind Keshri; M. M. Singh; Suprabhat Ray (Medicinal Chemistry Research, 2009)

RETRACTED ARTICLE: Engineered Polyallylamine Nanoparticles for Efficient In Vitro Transfection - Atul Pathak; Anita Aggarwal; Raj K. Kurupati; Soma Patnaik; Archana Swami; Yogendra Singh; Pradeep Kumar; Suresh P. Vyas; Kailash C. Gupta (Pharmaceutical Research, 2007)

Molecular cloning, stable expression and cellular localization of human α1-adrenergic receptor subtypes: effect of charcoal/dextran treated serum on expression and localization of α1D -adrenergic receptor - Sunil K. Khattar; Roop Singh Bora; Priyanka Priyadarsiny; Aarti Gautam; Dikshi Gupta; Atul Tiwari; Kamna Nanda; Rahul Singh; Anita Chugh; Vinay Bansal; Kasim Mookhtiar; Kulvinder Singh Saini (Biotechnology Letters, 2006)